Spindle-E Acts Antivirally Against Alphaviruses in Mosquito Cells - Varjak, Margus; Dietrich, Isabelle; Sreenu, Vattipally B.; Till, Bethan Eluned; Merits, Andres; Kohl, Alain; Schnettler, Esther (Viruses, 2018)
Mosquitoes transmit several human- and animal-pathogenic alphaviruses (Togaviridae family). In alphavirus-infected mosquito cells two different types of virus-specific small RNAs are produced as part of the RNA interference response: short-interfering (si)RNAs and PIWI-interacting (pi)RNAs. The siRNA pathway is generally thought to be the main antiviral pathway. Although an antiviral activity has been suggested for the piRNA pathway its role in host defences is not clear. Knock down of key proteins of the piRNA pathway (Ago3 and Piwi5) in Aedes aegypti-derived cells reduced the production of alphavirus chikungunya virus (CHIKV)-specific piRNAs but had no effect on virus replication. In contrast, knock down of the siRNA pathway key protein Ago2 resulted in an increase in virus replication. Similar results were obtained when expression of Piwi4 was silenced. Knock down of the helicase Spindle-E (SpnE), an essential co-factor of the piRNA pathway in Drosophila melanogaster, resulted in increased virus replication indicating that SpnE acts as an antiviral against alphaviruses such as CHIKV and the related Semliki Forest virus (SFV). Surprisingly, this effect was found to be independent of the siRNA and piRNA pathways in Ae. aegypti cells and specific for alphaviruses. This suggests a small RNA-independent antiviral function for this protein in mosquitoes.